Autoimmune hepatitis: clinicopathological characteristics and histopathological diagnosis in the light of current views - Iżycka-Świeszewska, Ewa; Walkusz, Natalia; Zieliński, Piotr; Sikorska, Katarzyna (Clinical and Experimental Hepatology, 2025)
The diagnosis of autoimmune hepatitis (AIH) is based on clinical criteria and histopathological findings. Interpretation of lesions observed in liver biopsy specimens, in cases of suspected AIH, requires correlation with clinical data and communication between hepatologists and pathologists. The diagnostic criteria have been modified over the years, and the latest guidelines were proposed in 2022. Implementation of the current recommendations improves diagnostic accuracy for autoimmune hepatitis and related pathologies. This article presents the clinicopathological characteristics of AIH and an overview of the histopathological diagnostic approach in the light of the modern guidelines.